PERAN PEMUDA DALAM MENCEGAH PAHAM RADIKALISME - Mulyadi, Mulyadi (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA, 2017)
This article discusses the role of youth in preventing the idea of radicalism in Indonesia. The data in this article were collected through references such as books, journals, newspapers, and the internet. This study found that radicalism is a common phenomenon that can occur in a society with various motives; social, political, cultural and religious that were characterized by violent, extreme and anarchic actions as a form of rejection the symptoms. Youth as the next generation is the main target of radical adherents. This is possible because youth are easily instigated with the wrong view and mind associated with radicalism. Therefore, with its diverse roles, youth can prevent this radicalism in various ways. First through the increase of education knowledge and understanding the religion. Second, read a lot of references. Third, always want to improve themselves, and the last set the goal of life.